Insights Into the Changing Landscape of Coronavirus Disease 2019 - Escobedo, Ruby A.; Kaushal, Deepak; Singh, Dhiraj K. (Frontiers in Cellular and Infection Microbiology, 2022)
Coronavirus disease 2019 (COVID-19) is a highly contagious, infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which emerged in late 2019 in Wuhan China. A year after the World Health Organization declared COVID-19 a global pandemic, over 182 million confirmed cases and approximately 4 million deaths have been reported worldwide. In this multidisciplinary review, we summarize important insights for COVID-19, ranging from its origin, pathology, epidemiology, to clinical manifestations and treatment. More importantly, we also highlight the foundational connection between genetics and the development of personalized medicine and how these aspects have an impact on disease treatment and management in the dynamic landscape of this pandemic.